Enhanced selective enrichment of partial nitritation and anammox bacteria in a novel two-stage continuous flow system using flat-type poly (vinylalcohol) cryogel films. (March 2020) - Choi, Minkyu; Chaudhary, Ramjee; Lee, Minjoo; Kim, Jihyun; Cho, Kyungjin; Chung, Yun-Chul; Bae, Hyokwan; Park, Joonhong
Graphical abstract: Highlights: Stable PN with high AOR 1.68 ± 0.12 kg N m −3 d −1 in short acclimation of 8 days. Flat-type PVAcryogel elevated endurance of immobilized anammox bacteria to O2 shock. A novel two-stage PN-anammox system achieved 90% N removal at short HRT of 7.7 h. Microbial analysis confirmed enhanced selective growth of AOB and anammox bacteria. Abstract: To improve stability of nitrogen removal in partial nitritation (PN)-anammox process, flat-type cryogel films using poly (vinylalcohol) named as FT-CPVAF were applied in continuous reactors. Stable PN operation was maintained with short acclimation of 8 days and ammonium oxidation rate of 1.68 ± 0.12 kg N m −3 d −1 comparatively higher than previous studies. The nitrogen removal, initially inhibited by an oxygen shock, was immediately reactivated with short lag-period by immobilization of anammox bacteria in FT-CPVAF. A novel two-stage PN-anammox process was operated in a continuous flow using FT-CPVAF for treatment of ammonium-rich synthetic wastewater (influent 315 mg NH4 + -N L −1 ) showing 89.6 ± 0.76% of nitrogen removal at short hydraulic retention time (7.7 h). The use of FT-CPVAF enhanced selective enrichment of AOB and anammox bacter ia confirmed by high-throughput sequencing of i.e., relative abundances of Nitrosomonas europaea C-31 (37.14% in PN reactor) and ' Candidatus Jettenia caeni' (34.36% in anammox reactor).